PERLINDUNGAN HUKUM BAGI KREDITOR DALAM PENGGUNAAN BASE TRANSCEIFER STATION (BTS) SEBAGAI OBJEK JAMINAN FIDUSIA DALAM PERJANJIAN KREDIT - Malikhatun Badriyah, Siti (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
The development of telecommunications business major effect on development. However, this requires a relatively large funds , so that the telecommunications service provider is in need of funds from the bank to the credit agreement . Bank has a big risk in lending this , so we need guarantees, one of which fiduciary guarantee with objects Base Transceiver Station . The purpose of this study was to determine and analyze the use of Base Transceiver Station in the credit agreement and what if the debtor defaults. The researchÂ method is a normative juridical. From the results it can be seen that the Base Transceiver Station ( BTS ) is a moving object that can be the object of fiduciary guarantee . If the debtor defaults , BTS can be executed in accordance with the stipulated in Fiduciary Guarantee Act.